Isolated hemolytic anemia: an unusual manifestation of occult malignancy - Matthew J. Butler; Ming Yin; Fahd Quddus (Hematology Reports, 2014)
Hemolysis is an uncommon and usually late complication of malignancy, and very rarely the presenting feature. Cancer-associated hemolysis may be immune-mediated, or may result from thrombotic microangiopathy accompanied by thrombocytopenia. We describe an unusual case of isolated hemolysis in the setting of occult metastatic breast cancer. The patient initially presented with symptomatic anemia, with evidence of hemolysis but with negative direct antiglobulin testing and a normal platelet count. Subsequent investigation discovered metastatic adenocarcinoma of the breast involving bone marrow. Hemolysis worsened despite initial treatment with cytotoxic chemotherapy and a trial of corticosteroids, but later resolved with aromatase inhibitor therapy.